A hybrid online-offline project-based learning model with a tractor hydraulic leveling system case for hydraulic and pneumatic transmission education - Wang, Jiaxin; Li, Jun; Hu, Teng (Frontiers in Education, 2025)
This study develops a hybrid Project-Based Learning (PBL) model integrating online-offline instruction for Hydraulic and Pneumatic Transmission. Using an intelligent tractor leveling system case, we implemented the approach with 93 undergraduates (test group) versus 70 undergraduates (control group). Results showed the test group achieved significantly higher theoretical test average score (70.4 vs. 67.9, p < 0.05) and lower failure rates (2.15% vs. 8.57%). Questionnaire surveys revealed greater satisfaction with teaching methods (1.52 vs. 1.96) and outcomes (1.92 vs. 2.21), with over 80% reporting improved practical understanding. The study demonstrates how research projects can effectively enhance engineering education through structured PBL implementation.